Effect of n-hexane extract of Nigella sativa on gentamicin-induced nephrotoxicity in rats - Begum, Nasim A.; Dewan, Zesmin F.; Nahar, Nilufar; Mamun, M. I. Rouf (Bangladesh Journal of Pharmacology, 2006)
The present study investigated whether the administration of the n-hexane extract of the Nigella sativa Linn. (kalajira) ameliorates gentamicin-induced nephrotoxicity in rats. Gentamicin (100 mg/kg/day for 7 days) was administered and nephrotoxicity was evaluated biochemically (significantly decreased reduced glutathione in renal cortex and significantly increased serum creatinine and serum urea) and histologically (moderate degree of proximal tubular damage). The n-hexane extract of N. sativa (5 mL/kg/day) was administered as pre-, post- and concomitant treatment for 7 days in the nephrotoxic rats. Statistically significant amelioration in all the biochemical parameters supported by significantly improved renal cortical histology was observed in the n-hexane extract of N. sativa treated nephrotoxic rats, which was more evident in the post-treatment group than the pre-treatment and the concomitantly-treated group. It is suggested that some ingredients contained in the n-hexane extract of N. sativa effected in ameliorating the signs of nephrotoxicity and that the specific active principle of the n-hexane extract of N. sativa responsible for this amelioration if obtained, would be more useful.